Evaluation of the antioxidant activity of phenols and tannic acid determination with Mn3O4 nano-octahedrons as an oxidase mimic. Issue 20 (21st August 2015) - Zhang, Xiaodan; Huang, Yuming
Abstract : Mn3 O4 nano-octahedrons as an effective oxidase mimic for the preliminary assessment of phenols' antioxidant activity and visual determination of tannic acid were demonstrated. Abstract : In this paper, we successfully synthesized novel Mn3 O4 nano-octahedrons using a simple hydrothermal method and demonstrated that the prepared Mn3 O4 nanoparticles (NPs) exhibited highly intrinsic oxidase-like activity and could catalyze the reaction of TMB, ABTS and OPD to produce a typical color reaction in the absence of H2 O2 within minutes. Compared with other non-noble metal NPs oxidase nanozymes, the affinity of Mn3 O4 NPs to TMB was increased by at least 35% according to the K m values. It was deduced that O2 ˙ − and few OH˙ radicals were produced during the catalytic reaction. Then, the addition of twelve phenols to the TMB–Mn3 O4 NP system led to the fading of the solution by different degrees based on the antioxidant activity of the phenols. Thus, preliminary assessment of the antioxidant ability of twelve phenols using TMB decolorization assays was realized based on the excellent oxidase-like properties of the Mn3 O4 NPs. Finally, under the optimum conditions, visual determination of tannic acid (TA) was realized and the detection limit was 19 nM with a linear range from 0.05 to 1.4 μM. The proposed method was successfully used to determine TA in tea samples.